PENERAPAN STRATEGI PEMBELAJARAN OUTING CLASS UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Fitri Jannah; Iis Aprinawati; Yenni Fitra Surya; Fadhilaturrahmi; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed at describing the increase of descriptive essay writing skill on Indonesian Language subject at the fifth grade of State Elementary School 006 Pasir Sialang District through Outing Class learning strategy. It was classroom action research. The subjects of this research were a teacher and 18 students. The objects were Outing Class strategy and descriptive essay writing skill. This research was conducted for two cycles, and every cycle comprised two meetings. Observation, test, and documentation were the techniques of collecting data. The technique of analyzing data was descriptive analysis with percentage. The research findings and data analyses showed that descriptive essay writing skill before the action was still low, and it was 72% or on poor category. After the improvement action by using Outing Class learning strategy was conducted in the first cycle, descriptive essay writing skill increased to 76,1%, and it was on good enough category. In the second cycle, descriptive essay writing skill increased again to 84,8%, and it was on very good category. Therefore, it could be concluded that the implementation of Outing Class learning strategy could increase descriptive essay writing skill on Indonesian Language subject at the fifth grade of State Elementary School 006 Pasir Sialang.